1976
DOI: 10.1021/jm00227a015
|View full text |Cite
|
Sign up to set email alerts
|

Cellular pharmacodynamics of several anthracycline antibiotics

Abstract: Alterations in the C-9 side chain of the anthracycline antibiotics, adriamycin and daunorubicin, have a profound effect on antibiotic uptake and accumulation by cultured L1210 cells. The degree of inhibition of DNA and RNA biosynthesis in the L1210 cells is directly related to the cellular uptake and accumulation of the drug analogues. Polar drug metabolites, daunorubicinol and adriamycinol, retain inhibitory activity against nucleic acid metabolism but have a decreased membrane binding and permeability. Cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(14 citation statements)
references
References 3 publications
2
12
0
Order By: Relevance
“…Using flow cytometry, we demonstrated rapid accumulation of all the anthracyclines in both cell types within minutes of incubation, which is in agreement with previous in vitro and in vivo findings of rapid influxes of anthracyclines across cellular membranes (Meriwether & Bachur, 1972;Egorin et al, 1974;Bachur, 1976). In both hepatoma cell lines, the fluorescence of DNR and ACL reached a plateau within 15 min.…”
Section: Discussionsupporting
confidence: 91%
“…Using flow cytometry, we demonstrated rapid accumulation of all the anthracyclines in both cell types within minutes of incubation, which is in agreement with previous in vitro and in vivo findings of rapid influxes of anthracyclines across cellular membranes (Meriwether & Bachur, 1972;Egorin et al, 1974;Bachur, 1976). In both hepatoma cell lines, the fluorescence of DNR and ACL reached a plateau within 15 min.…”
Section: Discussionsupporting
confidence: 91%
“…At identical doses, daunorubicin caused considerably less histamine release in the dog than did doxorubicin. This variation in response might be explained by the differences in structural characteristics of doxorubicin and daunorubicin, since the slight difference in structure between the 2 compounds leads to differences in membrane transport, intracellular accumulation and physiologic handling [16]. The reason a quantitative difference was not detected in the present studies is not known, but could be related to a difference in the route of administration or in the responsiveness of the mast cells of the 2 species.…”
Section: Discussionmentioning
confidence: 55%
“…Eichholtz-Wirth [2], Andersson et al [12] and other authors [4,6,8] have also observed that the incorpora tion of anthracyclines into cells was not linear with time, except in some cases during the first 30 min. However, different results have been obtained con cerning the relationship between cytotoxicity and total drug exposure.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous experimental systems have been de veloped in order to understand its cellular pharmaco logy and that of daunorubicin, a related anthracycline mostly active in vivo against leukemias. Those anti cancer drugs, or their derivatives, have been studied especially on HeLa cells [2], CHO cells [3], L 1210 cells [4], P388 cells [5,6], Friend leukemia cells [7], Ehrlich ascites tumor cells [8,9] and sarcoma 180 cells [10]. Cellular pharmacology studies of these drugs have also been conducted on normal cells such as fibro blasts [11] or bone marrow cells [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation